Pattern of neck metastasis in carcinoma of oral tongue-a prospective study of north eastern people - Saikia, Jyotish; Sarma, Mridul Kumar; Deka, Muktanjalee; Bharadwaj, Barasha Sarma (International Journal of Research in Medical Sciences, 2022)
Background: North eastern part of India is one of the most vulnerable regions for all sites of cancer. There is various literature regarding the pattern of cervical metastasis from different sub sites of oral cavity, however there are very few studies from the north eastern part of India, which reports one of the world highest number of cases. The aim and objectives of this study were to study the pattern of cervical lymph node metastasis in relation to prognostic factor like histological grading, laterality, depth of invasion, lymphovascular and perineural invasion and worst pattern of invasion. Methods: A prospective study of 20 patients who had undergone surgery for carcinoma of oral tongue was conducted in State cancer institute in department of Head and neck oncology from January 2020 till June 2021. Out of 20 patients included in the study 6 (30%) were females and 14 (70%) were males. Results: Clinically 9 patients had palpable nodes but pathologically nodes were positive in 10 patients whereas when a node was clinically not palpable in 11 patients, patients was pathologically nodes negative only in 10 patients.2 patients had isolated II involvement. 1 patient has I(b) and level II involvement. 4 patients had level II and III together. Two patients had level II and level IV involvement. 1 patient had level I(A), I(B), III and IV involvement. None of the patient had level 5 involvements. Conclusions: DOI, WPOI and tumor differentiation are the important prognostic parameters. We would also like to suggest surgical excision of the tumor and measurement of WPOI, DOI and assessment of histological grading to be done from frozen section for determining the type of neck dissection in T1/T2 N0 cases.